[College of Education honored its outstanding alumni] - College of Education, De La Salle University (Animo Repository, 1994)
The College of Education honored its outstanding alumni during the celebration of the 30th anniversary of the College of Educations' graduate school. Among those awarded were Herminia Torres, Evelia Orbeta, Fe Tawagon, Rommel Salvador, and Imelda Villar.